"Realismo" e subalternidade na narrativa brasileira contemporânea: o caso de Tropa de elite - Vinícius Gonçalves Carneiro (Estudos de Literatura Brasileira Contemporânea)
This article discusses the polemic Brazilian movie Elite squad. To understand the power games behind the movie and its reception, it is important to contextualize Elite squad in the contemporary Hollywood production, in a hypothetical Brazilian Realism tradition and in the cinematographic and literary representation of the subaltern. After that, using Bakhtin’s dialogism, it will be possible to analyze how some characters, such as the woman, the poor and subordinate, are oppressed by Captain Nascimento.